PELATIHAN PEMERIKSAAN TAJAM PENGLIHATAN PADA SISWA KELAS 5 SD GEDONGAN I, COLOMADU, KARANGANYAR - Sutrisna, Em; Hanwar, Dedi; Indrayudha, Peni; Sujono, Tanti Azizah (WARTA, 2007)
Seeing is crucial aspect in life includes in the field of education. Ifit is not cured the reduction ofÂ  sharpness of seeing/visus can affect thestudent ability to study. This action is done to detectÂ  this reduction early.Therefore, the eyes will not be getting worse. The research is done bytraining and demonstrating how to check visus. The location of the researchis SD Gedongan I, Gedongan, Colomadu, Karanganayar. The 31 studentsare checked. The result is that there are 3 students have visus with miop.All the students can participate in this research well.